Characteristics Of Physical And Chemical Properties Of Soil After Gold Processing (Case Study Of Unlicensed Gold Mining In The District Sumbawa Regency, Indonesia) - Hamkary Salam, Riza; Suwardji, Suwardji; Fauzi, Taufik; Kusnarta, IGM (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
The purpose of this study was to analyze the physical and chemical characteristics of the soil used for unlicensed gold processing in West Sumbawa Regency. This research was carried out in Kuang Village, Taliwang District, West Sumbawa Regency in September 2023. The criteria for soil sampling location is that the activity of the spindle has been inactive for 5 years, using mercury as a material for gold extraction and is in the home environment. This study was conducted by quantitative descriptive method or direct observation in the field and soil analysis in the Laboratory of soil chemistry and Biology, Faculty of Agriculture, University of Mataram. Furthermore, soil sampling was carried out using purposive sampling method or based on purpose with consideration of potential pollution. Based on the results, it can be seen that the physical characteristics of soil including clay with volume weight, specific gravity and porosity are quite dense soil with poor infiltration, while the chemical characteristics of soil include low fertility of both C-organic, CEC, soil pH, N and P soil. The concentration of Hg found in soil ranges from 1.42-15.83 ppm. In this case, mercury contaminated soil needs to be remediated using environmentally friendly materials, cheap and the availability of many in nature. Efforts that can be done is the use of green technology using phytoremediator plants and soil improvement materials, namely biochar. Therefore, it is necessary to conduct further research aimed at reducing the availability and mobility of mercury in the soil